" Getting a Grand Falls Job": Migration, Labour Markets, and Paid Domestic Work in the Pulp and Paper Mill Town of Grand Falls, Newfoundland, 1905-1939 - Botting, Ingrid Marie (Memorial University, 2000)
While it has been generally understood that domestic service was an institution of particular importance to working-class women and to middle-class householders in North America in the late 19th and early 20th centuries, we still know little about the interwar years, a period during which the occupation declined in overall importance, but still defined many women's working lives. In the 1920s and 1930s, a vast majority of women who grew up in Newfoundland's coastal communities, where household production and the family fishery remained the mainstay of the economy, spent part of their lives performing domestic tasks for pay. To begin to understand the historical and cultural significance of domestic service to women's lives in Newfoundland, this dissenation uses a case-study approach. It focuses on the pulp and paper mill town of Grand Falls, where there was a steady demand for domestics by mill workers and their families, the town's elite, and hotels and boarding houses during the 1920s and 1930s. One of a number of single-resource towns supported by Newfoundland's economic diversification policies of the late 19th and early 20th centuries, Grand Falls was built in the interior of the island by the Harmsworth brothers of Britain in 1905. By tracing domestics' lives and experiences from countryside to company town, into the household = as workplace - and then into their married lives, the study explores themes relating to the gendered nature of uneven development. For instance, many Grand Falls employers shared much in common with the women they hired, in terms of religion, ethnicity and social origin., which raises interesting questions about the gender and class dimensions of an employer/employee relationship that has traditionally been characterized as one of domination and subordination. It also considers that relations of gender and class within the company town were formed in conjunction with factors such as migration patterns, pre-existing concepts of the gender division of labour within household production, company paternalism and social stratification within the workplace, the household and the town. The ways in which these factors overlapped and shaped the lives of domestics forms the backdrop of this study.

Labour Organization and Unions - Rennie, Rick; Botting, Ingrid Marie; Inglis, Gordon (Newfoundland and Labrador Heritage, 1998)
Until well into the 20th century, Newfoundland and Labrador's primary economic activity was in the fisheries. Most of the workforce was in the inshore cod fishery, a small-boat operation in which family enterprises caught, split, salted and dried the fish to produce a finished product that was traded to a merchant. Fishers were not wage workers but commodity producers, like farmers. Even in the Labrador and Grand Banks fisheries and the annual seal hunt, the workers were treated as independent contractors, paying for their own gear and supplies and receiving shares rather than wages. --Introduction